Networking of firms in Industrial Clusters: A case of Sports Goods Cluster ofJalandhar - Kalra, Priya; Kumar, Prem; Dhindsa, Paramjeet Kaur (Gyan Management Journal, 2011)
This paper is an attempt to identify the factors determining the formation of networks in sports goods cluster of ]alandhar. Factor Analysis is applied to find out small set of uncorrelated variables and to replace the large set of correlated variables. The Principal Component Analysis through Orthogonal Rotation with Vari max method is used for extracting the factors. Three set of factors are found affecting the growth of spors goods cluster ofjalandhar. These are formation of informal groups, presence of business development services and presence of trust between the firms.
Keywords: Cluster; Factor Analysis; Networks